Development of Monitoring Control System in Domestic Water Home Tank - Norhafizan Majid; Zarina Yusof (Civil Engineering Dept, Balikpapan State Polytechnics, 2025)
This study explores the development of an innovative water quality control device for residential tanks, aimed at enhancing water safety and management. Ensuring clean and safe water in home tanks is a growing concern due to variable water quality and maintenance challenges. Traditional methods of water quality monitoring are often manual and inadequate for real-time intervention. The study aims to design a smart control system that provides continuous monitoring, real-time alerts, and automated corrective actions for residential water tanks. A prototype device was developed incorporating sensors for pH, turbidity, and temperature measurements. Data is collected and analyzed using IoT technology, with results displayed on a mobile application. The system features automated controls for water treatment processes and employs machine learning for predictive maintenance. The device successfully provided realtime monitoring and automated responses to water quality issues, significantly improving water safety and maintenance efficiency. Future improvements include expanding sensor capabilities, enhancing the predictive analytics and integrating with other home automation systems to further streamline water management processes.